Isoform-selective inhibitory profile of 2-imidazoline-substituted benzene sulfonamides against a panel of human carbonic anhydrases. (1st November 2016) - Supuran, Claudiu T.; Kalinin, Stanislav; Tanç, Muhammet; Sarnpitak, Pakornwit; Mujumdar, Prashant; Poulsen, Sally-Ann; Krasavin, Mikhail
Abstract: A series of novel benzene sulfonamides (previously evaluated as selective cyclooxygenase-2 inhibitors) has been profiled against human carbonic anhydrases I, II, IV and VII in an attempt to observe the manifestation of the well established "tail" approach for designing potent, isoform-selective inhibitors of carbonic anhydrases (CAs, EC 4.2.1.1). The compounds displayed an excellent (pKi 7–8) inhibitory profile against CA II (a cytosolic anti-glaucoma and anti-edema biological target) and CA VII (also a cytosolic target believed to be involved in epilepsy and neuropathic pain) and a marked (1–2 orders of magnitude) selectivity against cytosolic isoform CA I and membrane-bound isoform CA IV. The separation of the CA II and CA IV (both of which are catalytically active isoforms, highly sensitive to sulfonamide-type inhibitors) is particularly remarkable and is adding significantly to the global body of data on the chemical biology of carbonic anhydrases.